Switzerland : Technical Note-Macroprudential Institutional Arrangements and Policies. (IMF Staff Country Reports; Country Report ;, 2014)
This Technical Note on Macroprudential Institutional Arrangements and Policies on Switzerland highlights that macroprudential prudential powers and responsibilities are split across agencies. There is one dedicated macroprudential tool, the Counter Cyclical Buffer, which has a specified framework for decision making and consultation. Developments in real estate and mortgage lending are important systemic concerns. Very loose monetary policy has driven interest rates down to historically low levels, accelerating mortgage lending and bringing total mortgage debt to more than 140 percent of gross domestic product. The authorities have taken measures to address these risks. It is recommended that transparency and accountability could be strengthened by highlighting cross agency activity and policy analysis related to financial stability and macroprudential policies to the public. In a medium-term perspective macroprudential arrangements should be reviewed while considering placing responsibility and powers for macroprudential policies with one institution or committee. Additional measures may be needed. Mortgages to businesses and for commercial purposes deserve further attention and measures.